Kultūras un radošo industriju aktuālu jautājumu risināšanas iespējas Eiropas Savienības un Latvijas sociālekonomiskās attīstības veicināšanai - Šmeļova, Natālija (Latvijas Universitāte, 2012)
Maģistra darbs „Kultūras un radošo industriju aktuālu jautājumu risināšanas iespējas Eiropas Savienības un Latvijas sociālekonomiskās attīstības veicināšanai” ir daudznozaru pētnieciskais darbs. Teorētiskajā daļā tika veikts apjomīgs pētījums par kultūras un radošo industriju (KRI) jēdziena vēsturisko izcelsmi, definīcijas evolūciju, tika izpētīta starptautiska pieredze KRI politikas veidošanā. Darba ietvaros autore izpētīja visus ievērojamākos pētījumus par Latvijas KRI un to ietekmi uz nozares politikas veidošanos. Praktiskajā daļā tika rūpīgi izpētītas jaunākās KRI attīstības tendences Latvijā, apskatot visjaunākos nozares politikas veidošanas dokumentus, kā arī notikušos KRI veltītos starptautiskos seminārus, kas norisinājās ar Latvijas amatpersonu piedalīšanos. Papildus darbā izpētīta un izanalizēta radošās uzņēmējdarbības attīstība Latvijā un KRI atbalsta mehānismi. Darbā sniegts ieskats arī Rīgā izveidojušos radošo kvartālu darbībā un to nozīmē turpmākai radošās uzņēmējdarbības attīstībai Latvijā. Atslēgas vārdi: Kultūras un radošās industrijas, Kultūras un radošo industriju definīcija, Kultūras un radošo industriju attīstība Latvijā, Radošo industriju politika Latvijā, Radošie kvartāli

The topic of Master’s Thesis is „Possibilities for Dealing with Challenges Presented by the Culture and Creative Industries for the Promotion of Socio-economic Development of European Union: Latvian case”. The study is multidisciplinar research that examines and analyses the influence of culture and creative industries on the social and economic welfare of European union, focusing on the example of Latvia. Theoretic part of current Master’s Thesis gives an overview on the historical background of the term ‘culture and creative industries’, as well as presents the evolution of the definitions of it. The international experience of the culture and creative policy making is being examined in this research, with focus on the United Kingdom, Estonia, Finland and Sweden, with giving reasoning for such choice. As well, in the framework of current Master’s Thesis the author analyses the most authoritative researches about culture and creative industries in Latvia and their impact on policy making in the country. In the framework of the practical part of the Master’s Thesis the most recent development tendecies of culture and creative industries in Latvia were examined, giving the overview of latest policy making documents and international and local conferences, that took place in Latvia with attendance of government officials. Additionaly the Master’s Thesis presents an overview on the creative enterpreneurship in Latvia and the culture and creative industries support instruments available. The creation of culture and creative quarters in Riga and its influence on further creative enterpreneurship development in Latvia is also being analysed in the framework of current research. Key words: Culture and creative industries, Definition of culture and creative industries, Development of culture and creative industries in Latvia, Creative industry policy in Latvia, Creative quarters
Possibilities for Dealing with Challenges Presented by the Culture and Creative Industries for the Promotion of Socio-economic development of European Union: Latvian case
Keywords: Ekonomika